Do you understand me? - Koborg Brøsen, Sofie (J. Kingsley, 2006)
Sofie Koborg Brøsen is eleven years old and, like other children of her age, goes to a mainstream school, loves reading comics and being with her family and her cat, Teddy. But Sofie is not the same as everyone else - she has autism spectrum disorder. Fed up of being misunderstood by her classmates, she has written a book about her world so others can learn to understand her, and vice versa. Sofie describes her day-to-day life in clear, unambiguous language and tells readers about things she finds difficult: being given too many instructions, disruptions to her routine, being teas.